2021
DOI: 10.1016/j.rser.2020.110198
|View full text |Cite
|
Sign up to set email alerts
|

Towards nearly zero-energy residential neighbourhoods in the European Union: A case study

Abstract: The European Union (EU) aims to establish a guideline that requires all new buildings to comply with nearly zero-energy buildings (NZEB) by 2030. This decision involves new technologies based on concepts that meet international standards. This research aims to review the literature on 'net zero-energy building' and analyses the possibility of applying this research on nine statistically representative neighbourhoods of the building stock'in Belgium, depending on the built density. All the areas, grouped into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 53 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…From this table, it was observed that renovation allows reducing the energy consumption between 9.7% and 35.5% in these three cities. Furthermore, the energy demand is 63% higher in the coastal region than in high altitude regions, which confirms the previous study carried out by Nematchoua et al [29][30][31][32]. In particular, in Table 7, it can be observed that, after the revision process, the zero-energy objective is respected (the sum of the energy demand and the green energy generated by some photovoltaic panels (PV) is equal to zero).…”
Section: Case Of Residence Building Located In the Tropical Regionsupporting
confidence: 86%
“…From this table, it was observed that renovation allows reducing the energy consumption between 9.7% and 35.5% in these three cities. Furthermore, the energy demand is 63% higher in the coastal region than in high altitude regions, which confirms the previous study carried out by Nematchoua et al [29][30][31][32]. In particular, in Table 7, it can be observed that, after the revision process, the zero-energy objective is respected (the sum of the energy demand and the green energy generated by some photovoltaic panels (PV) is equal to zero).…”
Section: Case Of Residence Building Located In the Tropical Regionsupporting
confidence: 86%
“…Research on net-zero and net-positive energy buildings has been reported (Athienitis and O’Brien 2015 ; Mehrjerdi et al 2019 ; Sun et al 2019 ), while the International Energy Agency included an annex on “Towards Net-zero Energy Solar Building” and Canada launched in 2011 the Smart Net-zero Energy Buildings Strategic Research Network ( http://www.solarbuildings.ca ). The net-zero and net-positive energy building concepts can be expanded to include transportation devices that are part of the building (Garmsiri et al 2016 ; Sun et al 2019 ) and to net-zero and net-positive energy communities (Rad et al 2017 ; Hachem-Vermette et al 2019 ; Karunathilake et al 2019 ; Nematchoua et al 2021 ).
Fig.
…”
Section: Illustrationmentioning
confidence: 99%
“…The technologies, construction design, and their operation have been presented in [13] and [14]. The research has generally focused on small residential systems [15][16][17] and to a lesser extent on industrial systems [18][19][20][21]. However, large industrial operators Different solutions have been investigated regarding accelerating the decarbonization process.…”
Section: Introductionmentioning
confidence: 99%